PUB30‐mediated downregulation of the HB24‐SWEET11 module is involved in root growth inhibition under salt stress by attenuating sucrose supply in Arabidopsis. Issue 5 (29th December 2022) - Wang, Yutao; Zhao, Huan; Xu, Liyuan; Zhang, Hantao; Xing, Hongjie; Fu, Ying; Zhu, Lei
Summary: One of the strategies that plants adopt to cope with an unfavorable environment is to sacrifice their growth for tolerance. Although moderate salt stress can induce root growth inhibition, the molecular mechanisms regulating this process have yet to be elucidated. Here, we found that overexpression of a zinc finger‐homeodomain family transcription factor, HOMEOBOX PROTEIN 24 ( HB24 ), led to longer primary roots than in the wild‐type in the presence of 125 mM NaCl, whereas this phenotype was reversed for the hb24 loss‐of‐function mutant, indicating a negative impact of HB24 on salt‐induced root growth inhibition. We then found that salt stress triggered the degradation of HB24 via the ubiquitin–proteasome pathway, as mediated by a plant U‐box type E3 ubiquitin ligase 30 (PUB30) that directly targets HB24. We verified that HB24 is able to directly bind to the promoters of Sugars Will Eventually be Exported Transporter 11/12 ( SWEET11/12 ) to regulate their expression in roots. Through genetic and biochemical assays, we further demonstrated that the HB24‐SWEET11 module plays a negative role in salt‐induced root growth inhibition. Therefore, we propose that under salt stress, PUB30 mediates HB24′s degradation, thereby downregulating the expression of SWEET11, resulting in reduced sucrose supply and root growth inhibition.